Pediatric capacity crisis: A framework and strategies to prepare for a pediatric surge - Diana M. Bongiorno; Miranda Ravicz; Nicole L. Nadeau; Kenneth A. Michelson; Elizabeth R. Alpern; Sage R. Myers; Margaret E. Samuels‐Kalow (Journal of the American College of Emergency Physicians Open)
Abstract A pediatric capacity crisis developed across the country in the Fall and Winter of 2022 due to a combination of factors, including a surge in respiratory viruses, staffing shortages, and historical closures of inpatient pediatric units. The COVID‐19 pandemic and associated surge in critically ill adult patients demonstrated that health care systems and health care workers can quickly implement creative and collaborative system‐wide solutions to deliver the best care possible during a capacity crisis. Similar solutions are needed to respond to future surges in pediatric volume and to maintain a high standard of care during such a surge. This paper aims to build upon insights from the COVID‐19 and H1N1 pandemic responses and the 2022 pediatric capacity crisis. We provide specific recommendations addressing governmental/policy, hospital/health care system, and individual clinician strategies that can be implemented to manage future surges in pediatric patient volume.